DESIGN WEBSITE PORTAL INFORMATION CRIME-PRONE LOCATION USING THE CONCEPT OF CROWDSOURCING - Fairuz Iqbal Maulana; Choirul Huda (Merdeka Malang University, 2020)
Collaboration between individuals or groups is also commonly referred to as mutual cooperation is a characteristic and culture of the Indonesian nation that is driven by the awareness that we are social beings. Mutual cooperation can be in the form of providing useful information for others. This information can be in the form of a report that is processed into data and displayed on the website. Information about the security of a crime-prone location is the main topic of our research. This study designed a website that collects information about crime-prone areas in a mutual cooperation or crowdsourcing and displays the data on a map-based website. Users can share information on crime-prone areas with location-based systems on the map. Data from user information will be accumulated and displayed on the map of a website. This data is visualized using a color circle. The darker colors indicate that the crime rate of the location is high. The system on the proposed website is very useful for users who travel to unknown areas.